Establishment of Electoral Court in Indonesia: Problems and Future Challenges - Suparto, Suparto; Chaidir, Ellydar; Ardiansyah, Ardiansyah; Santos, Jose Gama (Universitas Negeri Semarang, 2023)
The primary aim of this research is to evaluate the imperative need for the establishment of a dedicated judicial body to address electoral disputes in Indonesia, particularly in light of the imminent concurrent elections scheduled for 2024 and the limited jurisdiction of the Constitutional Court in adjudicating such matters. This study employs normative legal research methodologies, incorporating legislative analysis, scrutiny of judicial precedents, and a comparative law framework as its principal approach. Uruguay serves as a pertinent comparative reference within the contextual parameters of this inquiry. The research findings unequivocally indicate the indispensability of instituting a specialized court for regional head elections, as mandated by Constitutional Court Decision Number 97/PUU-XI/2013. This imperative is substantiated by a series of legal arguments, namely: (a) the constrictive nature of the law's mandate, (b) the Constitutional Court's role as a constitutional enforcement institution rather than a court of justice, (c) the absence of an appellate process, contravening fundamental principles inherent to the electoral law system, (d) the quantitative approach to dispute resolution, impeding the attainment of justice, and (e) the presence of a distinct judicial system, engendering uncertainty and impeding the realization of justice, certainty, and expediency within the election legal framework. The establishment of specialized courts for regional head elections in Indonesia is analogous to the implementation of analogous courts in Uruguay and Costa Rica. In both jurisdictions, specialized election courts function as distinct entities, operating autonomously from the conventional judicial powers vested in the Supreme Court or the Constitutional Court.